Effect of Hypothyroidism on the Histology of Sublingual Salivary Gland in Adult Albino Rats - Nida Qasim Hayat , Shahnila Nadir , Fauzia Qureshi, Nida Qasim Hayat , Shahnila Nadir , Fauzia Qureshi (Journal of Rawalpindi Medical College, 2017)
Background: To investigate histological changes in the sublingual salivary gland of hypothyroid albino rat. Methods: Twenty male albino rats were divided into two groups; control group (A) and an experimental group (B), each containing 10 albino rats. Group B was rendered hypothyroid by giving 0.02% solution of methimazole (MMI) daily in drinking water for 3-weeks. Sublingual glands were removed, fixed in Bouin’s solution and processed for light microscopy. H&E stain was used for histological analysis. Serum T3, T4 and TSH levels were determined by enzyme immunoassay to confirm hypothyroid state of the animal. Results:Statistically significant decrease in the concentrations of T3, T4 and a statistically significant increase in the serum concentration of TSH was observed when the experimental group was compared to the control.The microanatomy of sublingual gland revealed normal connective tissue elements of sublingual salivary gland in 40% cases. Increased connective tissue architecture was seen in 7(35%) cases of experimental group B (p˂.025). Hence in a total of 20 cases, 45% showed increased connective tissue component (p<0.007). Increased lipid tissue was evident in 50%, out of which 10% belonged to group A and the remaining 40% to group B. Dilated lumen of mucous tubules was evident in 15% cases in control group whereas 35% showed dilated lumen of mucous tubules in group B. The changes were non evident in a total of 10(50%) cases where 7(35%) cases were in group A and 3(15%) cases were in group B. Conclusion: There is a remarkable difference in the histology of sublingual gland in hypothyroid state. This change can be visualized in the form of increased connective tissue content and lipid deposition. There is also marked dilatation of lumen of mucous tubules